Robust adaptive backstepping tracking control for a flexible air-breathing hypersonic vehicle subject to input constraint. (January 2015) - Zong, Q; Wang, F; Su, R; Shao, SK
This paper presents a tracking control problem of flexible air-breathing hypersonic vehicle with input constraint and aerodynamic uncertainty. Without ignoring aero-propulsive and elevator-to-lift couplings, a control-oriented model including aerodynamic uncertainty is firstly established. Then a robust adaptive backstepping control scheme is designed, in which the control-oriented model does not need to be transformed into linear parameterization formulation. Upper bounds of the uncertain terms do not need to be known in advance, which are estimated online by designing robust adaptive laws. To further consider input constraint, a constrained robust adaptive backstepping controller is proposed to simultaneously handle input constraint and aerodynamic uncertainty. Finally, the compared simulation results show the effectiveness of the designed control strategy.